2017
DOI: 10.1016/j.amepre.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Perceived Social Isolation Among Young Adults in the U.S.

Abstract: Introduction Perceived social isolation (PSI) is associated with substantial morbidity and mortality. Social media platforms, commonly used by young adults, may offer an opportunity to ameliorate social isolation. This study assessed associations between social media use (SMU) and PSI among U.S. young adults. Methods Participants were a nationally representative sample of 1787 U.S. adults aged 19–32 years. They were recruited in October–November 2014 for a cross-sectional survey using a sampling frame that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
250
3
13

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 464 publications
(342 citation statements)
references
References 33 publications
13
250
3
13
Order By: Relevance
“…Our results are also consistent with previous reports that the younger generations trend to be heavier internet users and are more exposed to social media exposition than older people. 40 The reasons are multiple but mainly involve technical skills and availability of internet resources.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also consistent with previous reports that the younger generations trend to be heavier internet users and are more exposed to social media exposition than older people. 40 The reasons are multiple but mainly involve technical skills and availability of internet resources.…”
Section: Discussionmentioning
confidence: 99%
“…Some research has shown that social media negatively impacts consumer well-being. Specifically, heavy social media use has been associated with higher perceived social isolation, loneliness, and depression (Kross et al 2013;Primack et al 2017;Steers et al 2014). Additionally, Facebook use has been shown to be negatively correlated with consumer well-being (Shakya and Christakis 2017) and correlational research has shown that limiting social media use to 10 min can decrease feelings of loneliness and depression due to less FOMO (e.g., Bfear of missing out;^Hunt et al 2018).…”
Section: Combatting Loneliness and Isolationmentioning
confidence: 99%
“…Similarly, a longitudinal study showed that regular FB users tend to benefit from a rich offline social network [3]. Perceived social isolation seems, however, to increase with high involvement in social media use (including FB), as found in a recent study on representative US individuals aged 19–32 years [4]. Yet, because this was a cross-sectional study, causality cannot be established.…”
Section: Introductionmentioning
confidence: 99%